2004
DOI: 10.1086/382137
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Mental Retardation and Autism Are Associated with a Mutation in the NLGN4 Gene, a Member of the Neuroligin Family

Abstract: A large French family including members affected by nonspecific X-linked mental retardation, with or without autism or pervasive developmental disorder in affected male patients, has been found to have a 2-base-pair deletion in the Neuroligin 4 gene (NLGN4) located at Xp22.33. This mutation leads to a premature stop codon in the middle of the sequence of the normal protein and is thought to suppress the transmembrane domain and sequences important for the dimerization of neuroligins that are required for prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
504
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 700 publications
(535 citation statements)
references
References 28 publications
8
504
0
13
Order By: Relevance
“…Mutations in the neuroligin genes NLGN4 and NLGN3, also located on the X chromosome, have been detected recently in a few cases of autistic disorder or XLMR with and without autistic disorder, respectively. 47,48 It remains to be elucidated whether such rare cases of autism have common genetic causes with some forms of mental retardation. (iv) Interneurons in the CA3 region of the hippocampal complex play a significant role in controlling hippocampal neuronal excitability by interaction 4 The neurotransmitter serotonin is involved in neuronal excitability of interneurons in hippocampus with influence on dendritic atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the neuroligin genes NLGN4 and NLGN3, also located on the X chromosome, have been detected recently in a few cases of autistic disorder or XLMR with and without autistic disorder, respectively. 47,48 It remains to be elucidated whether such rare cases of autism have common genetic causes with some forms of mental retardation. (iv) Interneurons in the CA3 region of the hippocampal complex play a significant role in controlling hippocampal neuronal excitability by interaction 4 The neurotransmitter serotonin is involved in neuronal excitability of interneurons in hippocampus with influence on dendritic atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[251][252][253] One study 254 detected several other variants in NLGN3 and NLGN4X; however, only nominal significance for association with AD was found. As the NLGN4X nt1253del(AG) frameshift mutation found in one study 249 co-segregated with unspecific mental retardation and AD in one large family, it is likely that NLGN4X mutations might be rare single gene disorders causing AD and unspecific mental retardation. Owing to the rare occurrence of the observed variants in larger samples of individuals with AD, however, it is unlikely that the NLGN3 and NLGN4X genes play an important role in idiopathic autism.…”
Section: X-chromosomementioning
confidence: 99%
“…Accumulating evidence suggests involvement of the neuroligin family in autism and other neuropsychiatric disorders (Jamain et al., 2003; Laumonnier et al., 2004; Lawson‐Yuen, Saldivar, Sommer, & Picker, 2008; Philippe et al., 1999; Sindi, Tannenberg, & Dodd, 2014; Thomas et al., 1999). In 2003, a mutation in neuroligin 3 ( NLGN3 ; p.R451C) and a mutation in neuroligin 4X ( NLGN4X ; p.D396 fs) were reported in two unrelated Swedish autism families (Jamain et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, a mutation in neuroligin 3 ( NLGN3 ; p.R451C) and a mutation in neuroligin 4X ( NLGN4X ; p.D396 fs) were reported in two unrelated Swedish autism families (Jamain et al., 2003). Since then, several other mutations in the NLGN3 , NLGN4X , and NLGN4Y genes have been reported to be related to autism (Chih, Afridi, Clark, & Scheiffele, 2004; Daoud et al., 2009; Kuroda et al., 2014; Laumonnier et al., 2004; Lawson‐Yuen et al., 2008; Talebizadeh et al., 2006; Yan et al., 2005, 2008). In vitro and in vivo experiments have indicated that the autism‐related neuroligin mutations may affect synapse maturation and function.…”
Section: Introductionmentioning
confidence: 99%